Membangun Karakter Mulia pada Anak: Pertimbangan Pengenalan Hukum Islam Semenjak Dini - Rosdiana Rosdiana (PSGA LP2M IAIN Pontianak, 2015)
This writing elaborates the introduction of Islamic Law towards children as an attempt to build a noble character on them. The noble character or “akhlaq” in Islam is a result of implementing process in sharia (ibadah and muamalah) based on the strong foundation known as “aqidah” in Islam. Furthermore, all of the sharia stipulation grounded on the implementation of akhlaq and noble character. The relevance of the Islamic Law introduction and the character building is able to integrated through religion education taught by parents, school, and society. Moreover, religion education is considerably inadequate if it only concerns on the cognitive aspect, it also needs to learn about the emotional intelligence of the children. Thus, the importance of children understanding on Islamic Law is performed that the children could have a self-awareness towards the globalization, they could differentiate the right and wrong, and be able to make a great decision in their life, family, even society. Besides, the problems of religion education which tends to be more theoretic cannot be effective enough to be a ground of character building. So, Islamic Law for more mature children needs to be introduced through strengthening the right religious education. This writing, psychologically and philosophically, would like to address the significant point of introducing the Islamic Law to children. Therefore, parents and other environments have a great role in giving the examples about the studied materials.